Electrokinetic sample preconcentration and hydrodynamic sample injection for microchip electrophoresis using a pneumatic microvalve. Issue 3 (6th November 2015) - Cong, Yongzheng; Katipamula, Shanta; Geng, Tao; Prost, Spencer A.; Tang, Keqi; Kelly, Ryan T.
Abstract : A microfluidic platform was developed to perform online electrokinetic sample preconcentration and rapid hydrodynamic sample injection for zone electrophoresis using a single microvalve. The polydimethylsiloxane microchip comprises a separation channel, a side channel for sample introduction, and a control channel which is used as a pneumatic microvalve aligned at the intersection of the two flow channels. The closed microvalve, created by multilayer soft lithography, serves as a nanochannel preconcentrator under an applied electric potential, enabling current to pass through while preventing bulk flow. Once analytes are concentrated, the valve is briefly opened and the stacked sample is pressure injected into the separation channel for electrophoretic separation. Fluorescently labeled peptides were enriched by a factor of ∼450 in 230 s. This method enables both rapid analyte concentration and controlled injection volume for high sensitivity, high‐resolution CE.